Studies on Q-switching and mode-locking pulse generation in fiber cavity with saturable absorber / Ahmed Nady Eweis Aly - Ahmed Nady, Eweis Aly (2017)
Pulsed fiber lasers represent the state of the art in laser technology that hold a great promise for portable and powerful pulsed light sources. Saturable absorber (SA) is a key element in optical pulsed lasers. It enables generation of pulses in one of two possible regimes, passively mode-locked or passively Q-switched. Passively mode-locked fiber lasers are amongst the best pulsed sources available due to their simplicity and ability to create transform-limited optical pulses in the picosecond and femtosecond regimes, whereas passively Q-switched fiber lasers are generally used for generating high-energy pulses at relatively low repetition rates in the microsecond or nanosecond regime. Such lasers offer excellent pulse quality and there is no need for costly modulators as required in actively mode-locked or Q-switched lasers. In this study, numerical simulations of Q-switching and mode-locking operations in fiber cavity with SA have been developed. In the Q-switched laser model, the SA dynamics was taken into account. Peak power, repetition rate, and pulse duration have been calculated as functions of pump power. In the mode-locked laser model, the temporal change in saturable absorption has been taken into account. The effects of each component in the cavity (active fiber, passive fiber, and SA) have been investigated as well as the energetics and pulse properties for different fiber laser arrangements/configurations. Furthermore, novel cobalt oxide (Co3O4), vanadium oxide (V2O5), and nickel oxide (NiO) are introduced as SAs in generating Q-switched and mode-locked EDFL. A Q-switched EDFL is demonstrated utilizing Co3O4 nanocubes, which was embedded into a PEO film. The proposed laser generates a stable pulse train where the pulse repetition rate is tunable from 29.8 to 70.92 kHz and the pulse-width reduces from 10.9 to 5.02 μs as the pump power increases from 55 mW to 165 mW. A V2O5 Q-switched EDFL is established and centered at 1565 nm with 3-dB bandwidth of 1.12 nm and pulse duration of 5.6 μs at 165 mW pump power. A mode-locked EDFL based on V2O5-SA has been successfully demonstrated. The generated pulses have centre wavelength of 1559.25 nm with duration and repetition rate of 3.14 ps and 1 MHz, respectively. Another NiO Q-switched EDFL operates at 1561.2 nm with the minimum pulse duration of 5.2 μs at 95 mW pump power. The laser has a pulse repetition rate tunable from 19.57 to 52.18 kHz as the pump power increases from 25 mW to 95 mW. An ultrashort mode-locked EDFL is demonstrated using NiO based SA to generate optical pulses with 3-dB spectral width of about 2.85 nm centered at 1561.8 nm. The pulses have a duration of 950 fs with a repetition frequency of 0.96 MHz. The results indicate that these new SA materials have a great potential in ultrafast photonic applications.